Design, synthesis and cytotoxic activity of new 6-O-aroyl (−)-cleistenolide derivatives. (10th September 2021) - Benedeković, Goran; Popsavin, Mirjana; Kovačević, Ivana; Kojić, Vesna; Kesić, Jelena; Farkas, Sándor; Popsavin, Velimir
Abstract: Fifteen new analogues of (−)-cleistenolide (1 ) with aromatic ester groups at the C-6 position were designed and synthesized by multistep sequences. Steglich esterification of δ-pyrone 10 with selected aromatic acids (benzoic, cinnamic, and 4-substituted cinnamic acids) gave the corresponding 6- O -acyl derivatives 11 –15 . An original method was developed for the selective conversion of the primary benzyloxy group into the corresponding acetoxy function, giving five new bioisosteres (16 –20 ) for biological testing. Finally, the dibenzyl derivative 11 was converted to the corresponding diacetate 2 using the AcBr/Zn(OTf)2 reagent system. For the transformation of compounds 12 –15 into the corresponding 4, 7-diacetates (3 –6 ), in addition to Zn(OTf)2, it was necessary to use FeCl3 as a co-catalyst. The cleistenolide analogues thus obtained were tested for their in vitro antitumour activity The majority of compounds showed higher potency compared to lead 1 toward five of six investigated human tumour cell lines, but were almost completely inactive in the culture of normal foetal fibroblasts (MRC-5). The most potent antiproliferative activity was shown by 4, 7-di- O -benzyl derivatives 13 and 14, with IC50 values of 0.04 (HeLa) and 0.09 μM (Jurkat), respectively. Preliminary SAR analysis revealed some of the structural features important for the activity of this class of compounds. These are: the presence of unsubstituted cinnamate function at the C-6 position and the presence of an acetoxy group at the C-4 position. Graphical abstract: New analogues of (−)-cleistenolide were designed, synthesized and evaluated for their antitumour activity in vitro. Image 1 Highlights: New cleistenolide analogues were designed, synthesized and tested for their in vitro cytotoxicity. A new method for selective conversion of the primary OBn to AcO functions was developed. Ten analogues are more active than doxorubicin against A549 cells. Analogues are inactive to normal MRC-5 cells, and specific for tumour cells.